MUSIK SEBAGAI KRITIK SOSIAL: ANALISIS KOMUNIKASI DALAM LAGU 'BAYAR BAYAR BAYAR' OLEH BAND SUKATANI - Nita Talia (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
The song "Bayar Bayar Bayar" by Band Sukatani has sparked an interesting social phenomenon, with lyrics that explicitly criticize corruption within the police force. This study aims to analyze how the song shapes public discourse on police corruption through mass communication theory, agenda-setting, and framing. Using a qualitative approach and case study design, this research identifies the role of social media and mass media in disseminating the social critique conveyed through the song. The findings reveal that social media plays a key role in accelerating agenda-setting, while mass media frames the issue, thereby influencing public perception of the police institution. Lyrical analysis reveals that the song uses symbolism and metaphors to portray social injustice and corruption within the police. This research enriches mass communication theory literature and provides new insights into the use of music as social criticism in the digital era. The findings also emphasize the importance of freedom of expression and media literacy amidst the dominance of social media in shaping public opinion.